2008
DOI: 10.1038/gt.2008.169
|View full text |Cite
|
Sign up to set email alerts
|

A Kunjin replicon vector encoding granulocyte macrophage colony-stimulating factor for intra-tumoral gene therapy

Abstract: We have recently developed a non-cytopathic RNA repliconbased viral vector system based on the flavivirus Kunjin. Here, we illustrate the utility of the Kunjin replicon system for gene therapy. Intra-tumoral injections of Kunjin replicon virus-like particles encoding granulocyte colony-stimulating factor were able to cure 450% of established subcutaneous CT26 colon carcinoma and B16-OVA melanomas. Regression of CT26 tumours correlated with the induction of anticancer CD8 T cells, and treatment of subcutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 63 publications
(79 reference statements)
0
25
0
Order By: Relevance
“… 104 108 For example, Kunjin virus vectors expressing GM-CSF provided cure in more than 50% of mice with established subcutaneous CT26 colon carcinomas after intratumoral administration. 109 Moreover, regression of B16-OVA melanoma tumors was obtained after 5 days, with a cure rate of 67%. Subcutaneous administration of Kunjin GM-CSF particles resulted in tumor regression in CT26 lung metastasis in BALB/c mice.…”
Section: Examples Of Therapeutic Applications Of Oncolytic Virusesmentioning
confidence: 95%
“… 104 108 For example, Kunjin virus vectors expressing GM-CSF provided cure in more than 50% of mice with established subcutaneous CT26 colon carcinomas after intratumoral administration. 109 Moreover, regression of B16-OVA melanoma tumors was obtained after 5 days, with a cure rate of 67%. Subcutaneous administration of Kunjin GM-CSF particles resulted in tumor regression in CT26 lung metastasis in BALB/c mice.…”
Section: Examples Of Therapeutic Applications Of Oncolytic Virusesmentioning
confidence: 95%
“…In the context of flaviviruses, the granulocyte macrophage colony-stimulating factor (GM-CSF) expressed from a Kunjin virus vector was subjected to intratumoral administration in mice with subcutaneous CT26 colon carcinoma [ 62 ]. The treatment resulted in a cure of more than 50% of injected mice; tumors were undetectable 18 days after Kunjin-GM-CSF administration.…”
Section: Viral Vectorsmentioning
confidence: 99%
“…Related to cancer immunotherapy, a large number of studies have confirmed that self-amplifying RNA viruses can generate tumor regression, prolonged survival and even tumor protection in animal models for various cancers [ 8 ]. For instance, expression of GM-CSF from Kunjin virus particles resulted in tumor regression in a mouse melanoma model [ 93 ]. Moreover, VEE particles expressing PSCA (prostate stem cell antigen) demonstrated tumor protection in a prostate cancer model [ 94 ].…”
Section: Rna Stability Improvementsmentioning
confidence: 99%